Business Development Strategy to Develop and Sustain Small Family Business (Case Study: Huanghun Bird’s Nest) - Eunike Setiawan; Wawan Dhewanto (AIBPM Publisher, 2021)
Huanghun Bird's Nest is a family business that sells small-scale raw bird's nests (S.M.E.), which has been operating for 20 years in Banyuwangi. The development and growth of the Huanghun Bird's Nest are considered very slow, so the second generation started to develop the Huanghun Bird's Nest by producing finished swallow's nest products that can be directly consumed. This requires a special strategy that is suitable for a family business so that this business can successfully develop and survive. In Indonesia alone, 99% of family businesses are still classified as S.M.E.s. Hence the main objective of this study is to identify strategies to develop a small family business and make it sustainable. The mixed-method was chosen for this study to carry out an interpretive analysis of the subject. The collected data is used to explore internal and external environment analysis. The formulation stage uses internal and external analysis, which then forms a S.W.O.T. and then uses a T.O.W.S. analysis matrix to produce a suitable business strategy. In addition, the Ansoff Matrix was also carried out to find out what strategies will be used to develop this business. The goal of this research is to implement business development strategy to make Huanghun Bird’s Nest developed and sustainable using market development strategy.